Aristotle and Johnston on Hylomorphism and the Character of Objects: A Discussion Note - Panayides, Christos Y. (Problemos, 2021)
As M. Loux has recently reminded us, there are two basic strategies for explaining the character of particular objects, the ‘relational approach’ and the ‘constituent approach’. The prime example of a constituent approach would be Aristotelian hylomorphism. This article reveals three things. First, it gives a roadmap towards what the author considers to be the exegetically correct reconstruction of Aristotle’s hylomorphic theory. Second, it provides a presentation of the basic claims of a neo-Aristotelian hylomorphic theory, the one argued for by M. Johnston. Finally, it argues that regardless of whatever shortcomings it may have, Aristotle’s theory has an advantage over that proposed by Johnston. Unlike Johnston’s theory, it may give us a complete account of the character of a particular object.